The Reasons of Culling of Cattle in Dairy Cows Herd – a Review - Dziekiewicz-Mrugasiewicz, Małgorzata; Wierzbicka, Małgorzata (Polish Journal of Natural Sciences, 2021)
The culling of cows is an important element in dairy farming, which has a huge impact on the progress of breeding. Culling of animals in the herd is understood as the removal of the animal from the herd as a result of selling the animal to another farm, slaughter and death or euthanasia of animal. The reasons for culling can be divided into voluntary and involuntary or the division into economic and biological reasons. Economic culling (voluntary) is a conscious action of the breeder aimed at increasing the breeding and functional value of the herd, while biological culling is connected with occurrence of metabolic and infectious diseases as well as reproduction and limbs problems or sudden deaths of the animal. In recent years, biological culling has caused significant economic losses to the herd. Improving this can be achieved through intensive prevention and herd health monitoring.